2005
DOI: 10.1086/432762
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hepatitis C Virus Infection on HIV‐1 Disease Progression and Response to Highly Active Antiretroviral Therapy

Abstract: HCV serostatus did not affect the risk of HIV-1 disease progression, but the risk of liver disease-related deaths was markedly increased in HCV-seropositive patients. The overall virologic and immunologic responses to HAART were not affected by HCV serostatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
263
5
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(302 citation statements)
references
References 26 publications
22
263
5
12
Order By: Relevance
“…One of such virus is HCV, one of the most common causes of chronic viral hepatitis, which has remained the commonest cause of serious liver diseases among HIV-infected individuals [27][28][29][30] . As highlighted earlier, human immunodeficiency virus (HIV) and hepatitis C virus(H-CV) have common routes of infection making it possible for both viruses to co-infect the same individual 1,2,31 . Of the 32.2-38.8 million people living with HIV, about 7 million individual (approximately 20.0-25.0%) are reported to be co-infected with HCV.…”
Section: Discussionmentioning
confidence: 99%
“…One of such virus is HCV, one of the most common causes of chronic viral hepatitis, which has remained the commonest cause of serious liver diseases among HIV-infected individuals [27][28][29][30] . As highlighted earlier, human immunodeficiency virus (HIV) and hepatitis C virus(H-CV) have common routes of infection making it possible for both viruses to co-infect the same individual 1,2,31 . Of the 32.2-38.8 million people living with HIV, about 7 million individual (approximately 20.0-25.0%) are reported to be co-infected with HCV.…”
Section: Discussionmentioning
confidence: 99%
“…HCV may have a deleterious effect on HIV progression. The Swiss HIV Cohort study and others demonstrated that HCV infection was independently associated with an increased risk of progression to AIDS or death, despite a similar use of antiretroviral therapies in the coinfected group compared with the group infected with HIV alone [162][163][164]. A Swiss study also suggested that those patients with dual infection may be less likely to achieve a CD4 count rise of at least 50 cells/mL within 1 year of starting HAART than those with monoinfection.…”
Section: Natural Historymentioning
confidence: 97%
“…48,50,52 For example, although HIV replication in co-infected patients may, in theory, be stimulated by the persistent state of immune activation induced by chronic HBV replication and by the HBV protein HBx, 53 no significant effect of HBV carriage on HIV progression has been observed. 50 After initiation of HAART, virologic and immunologic responses are generally similar in both HCV/HIV 54,55 and HBV/HIV 56 -58 co-infected patients compared with those with HIV alone. Whether HBV, HCV, or human T-lymphotropic virus co-infection could influence seminal vesicle infection by HIV is currently unknown.…”
mentioning
confidence: 99%